Virtual reality exposure therapy in the treatment of fear of flying: a case report - Rothbaum, Barbara Olasov; Hodges, Larry; Watson, Benjamin A.; Kessler, G.Drew; Opdyke, Dan (Behaviour research and therapy, 1996)
The efficacy of virtual reality (VR) exposure therapy was examined for the fear of flying. Virtual reality exposure involved six sessions of graded exposure to flying in a virtual airplane. The specific contribution of anxiety management techniques (AMT) and the VR exposure was examined in a single case design. The subject was a 42-year-old female with a debilitating fear and avoidance of flying. All self-report measures of the fear and avoidance of flying decreased following AMT and decreased still further following VR exposure. A planned post-treatment flight was completed with anxiety measures indicating comfortable flight. The implications of this new medium for exposure therapy are discussed.